The Effectiveness of E-Learning in Light of the Spread of the Corona Pandemic from the Point of View of Teachers at King Faisal Primary School - Al-Khaibri, Ibrahim Saleh Hammoud (Advances in Social Sciences Research Journal, 2022)
The effectiveness of e-learning in light of the spread of the Corona pandemic from the point of view of teachers at King Faisal Primary School. Due to the Corona pandemic, educational institutions suddenly found themselves forced to switch to distance learning to ensure the continuity of the educational process, so they resorted to using the Internet, smartphones and computers to communicate remotely with students. This study seeks to reveal the effectiveness of e-learning in light of the spread of the Corona virus from the viewpoint of teachers at King Faisal Primary School in Yanbu, identifying obstacles to the use of e-learning, the level of interaction between students and teachers in the e-learning environment, and analyzing the main difficulties that teachers faced during the application of online learning in the hope of coming up with recommendations to address the phenomenon of weak motivation towards education among students and increase the interaction between teacher and student, and to develop practical and workable solutions to address weak learning motivation among students and weak interaction between students and teachers. This study released on the descriptive analytical method. To achieve the objectives of the study, the researcher formulated a questionnaire of (40) items, directed to teachers at King Faisal Primary School in Yanbu who applied e-learning during the Corona pandemic. The questionnaire was distributed to a sample of (38) teachers at King Faisal Primary School in Yanbu. The questionnaire's paragraphs dealt with four topics as follows: E-learning continuity: (14) paragraphs. Obstacles to e-learning: (10) paragraphs. Teachers' interaction with e-learning: (10) paragraphs. Students' interaction with e-learning: (6) paragraphs. The study confirmed the effectiveness of e-learning in light of the spread of the Corona virus from the teachers' point of view, and the results of the questionnaire demonstrated that the continuity of education was not affected by the Corona thanks to the transition to e-learning with the availability of all elements of the educational process. The study indicated that there are easy obstacles represented in the process of exchanging ideas and opinions with students through the Internet, which was naturally less effective when compared to the traditional teaching method. The study also stressed the need to raise the efficiency of teachers and train them on the most effective ways to deal with large numbers at once in e-learning platforms, and the need to strengthen the current evaluation mechanism.